Aleitamento materno na primeira hora de vida em maternidades privadas brasileiras participantes de um projeto de melhoria da qualidade da assistência - Rachael de Vasconcelos Alves; Maria Inês Couto de Oliveira; Rosa Maria Soares Madeira Domingues; Ana Paula Esteves Pereira; Maria do Carmo Leal (BMC, 2023)
Abstract Background The Baby-Friendly Hospital Initiative's Step 4 recommends: "support mothers to start breastfeeding as soon as possible after birth", thus contributing to the reduction of neonatal mortality. The objective of this study is to estimate the prevalence of breastfeeding in the first hour of life in private maternity hospitals participating in the "Adequate Childbirth Project", a quality-of-care improvement project, and to analyze determinants of this outcome. Methods Secondary analysis of data collected by the cross-sectional evaluative "Healthy Birth Study", conducted in 2017 in 12 maternity hospitals participating in the Adequate Childbirth Project, where 4800 mothers were interviewed, and hospital records were observed. Conditions that prevented breastfeeding at birth, such as maternal HIV-infection and newborns' severe malformations, were excluded. Multiple logistic regression was performed according to a hierarchical theoretical model. Results The prevalence of breastfeeding in the first hour of life was 58% (CI 95% 56.6-59.5%). Lower maternal education (aOR 0.643; CI 95% 0.528-0.782), lower economic status (aOR 0.687; CI 95% 0.504-0.935), cesarean section delivery (ORa 0.649; CI 95% 0.529-0.797), preterm birth (aOR 0.660; CI 95% 0.460-0.948) and non-rooming-in at birth (aOR 0.669; CI 95% 0.559-0.800) were negatively associated with the outcome. Receiving information during prenatal care about the importance of breastfeeding at birth (aOR 2.585; CI 95% 2.102-3.179), being target of the quality-of-care improvement project (aOR 1.273; CI 95% 1.065-1.522), skin-to-skin contact at birth (aOR 2.127; CI 95% 1.791-2.525) and female newborn (aOR 1.194; CI 95% 1.008-1.415) were factors positively associated with the outcome. Conclusions The private maternities participating in the Healthy Birth Study showed a good prevalence of breastfeeding in the first hour of life, according to WHO parameters. Prenatal guidance on breastfeeding at birth, being target of the quality-of-care improvement project and skin-to-skin contact at birth contributed to breastfeeding in the first hour of life.